Measuring Crop Coefficient For Vineyards - Al masraf, Sabah Anwer Dawood (Nahrain University College of Engineering Journal, 2016)
In this paper crop coefficient for vineyard was measure from water consumption or crop evapotranspiration in afield of vineyeard located in Travers City, Michigan State/ United State of America. The objectives were to find it varaities with time as plant grew, and to compare the predicted crop coefficient with the local available values (MSU) and with the recommended values by FAO. Measurements were conducted on the basis of soil water content and weather parameters to calculate crop evapotranspiration (consumptive use) and reference evapotranspiration by means of Penman-Monteith model, respectively. The results of the statistical analysis of error showed that the predicted crop coefficients were always less than the local values (Michigan State) for all months of study period except for August (late- mid of the season) where the predicated value was more than the local one. Additionally the absolute error showed that the lowest error was in June, July, and August and the highest value was in May with an average absolute error value for all months 0.2. While, the predicated crop coefficients were almost close to FAO values for all months except for May and August with an average absolute error value for all months 0.085. Moreover, the statistical analysis by using root mean square difference (RMSD), relative error (RE), and mean bias error (MBE) to compare predicated and FAO vineyard crop coefficient were: 0.099, 18% and 0.01, respectively, while for predicated and local values were: 0.25, 35%, and – 0.17, respectively.